2011
DOI: 10.1111/j.1365-2788.2011.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Brief Symptom Inventory (BSI) in psychiatric outpatients with intellectual disabilities

Abstract: As a result of the psychometric properties illustrated, this study supports the use of the BSI as a screener for psychopathology and a general outcome measure in people with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…() and Wieland et al . () found that the OCD scale in the BSI was replicated in an exploratory and confirmatory factor analysis respectively with people who have ID. However, Kellett et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…() and Wieland et al . () found that the OCD scale in the BSI was replicated in an exploratory and confirmatory factor analysis respectively with people who have ID. However, Kellett et al .…”
Section: Discussionmentioning
confidence: 94%
“…The alpha value of 0.93 for the BSI in this study is very high and similar to that reported by Wieland et al . ().…”
Section: Discussionmentioning
confidence: 97%
“…It has its own form of Routine Outcome Monitoring, using instruments especially developed for people with ID, but also instruments used in regular psychiatry, such as the Brief Symptom Inventory (Derogatis ; Wieland et al . ). Patients are informed at the beginning of the assessment that if data are used for research purposes, this is done in anonymous form.…”
Section: Methodsmentioning
confidence: 97%
“…Authors have also called for the investigation of Axis I comorbidity in individuals with ID including schizophrenia (Morgan, Leonard, Bourke, & Jablensky, 2008), MDD (Ailey, 2009;Lunsky & Palucka, 2004;Morin, Rivard, Cobigo, & Lé pine, 2010), manic symptoms (Gonzá lez & Matson, 2006), anxiety disorders (Hagopian & Jennet, 2008), antisocial personality disorder (Morrissey & Hollin, 2011), and general psychopathology (Matson, 1995;Taylor & Novaco, 2013;Wieland, Wardenaar, Fontein, & Zitman, 2012). Establishing the psychometrics of the PIMRA-II will allow researchers to further investigate the topic of comorbid psychopathology in individuals with ID.…”
mentioning
confidence: 97%
“…Previous researchers have found that psychiatric disorders are often missed in individuals with ID and psychometrically sound instruments are needed for this population (Wieland et al, 2012). Due to the diminished verbal abilities of some individuals with ID, psychometrically robust rating instruments to screen for psychopathology tailored to those with ID are essential (Havercamp & Reiss, 1997).…”
mentioning
confidence: 99%